Translation strategies in translating traditional medicine materials from Vietnamese into English = Chiến lược dịch tài liệu Y học cổ truyền từ tiếng Việt sang tiếng Anh - Nghiêm, Xuân Hải (2020)
This paper investigates translation strategies, including translation procedures and methods in translating traditional medicine terminologies and texts. In the first place, background knowledge of translation is reviewed in order to give readers an overview about translation definition, translation procedures and methods. All types of translation procedures as well as translation methods suggested by Newmark. P (1998) would be mentioned concisely in this part. Then, there are some sections for terminology analyses where people can find its definitions and characteristics. The next part provides an overall understanding on traditional medicine and the two outstanding features of terminologies in this area. Plus, an analysis on equivalence and non-equivalence between traditional medicine terms and modern medicine terms is also conducted so that readers can see differences between terms in the two medicines and how they affect the translation. The most important part is for finding out translation procedures and methods applicable in translating traditional medicine terminologies and texts. It is noticeable that translation methods to translate texts will be proposed basing on the author’s opinion and knowledge, whereas translation procedures to translate terminologies will be collected and synthesized from various materials.